Contemporary Logistics in China Transformation and Revitalization - Liu, Bing-lian.; Lee, Shao-ju.; Xiao, Jian-hua.; Wang, Ling.; Jiao, Zhi-lun.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Driven by decades of steady economic growth in China, logistics has now taken center stage in the nation$1 (Bs development plan, and both infrastructural construction and operations systems have been improved to propel logistics into a new era. This book, the second volume of the series on (3z(BContemporary Logistics in China,(3y (Bis a (3z(Bjust-in-time(3y (Bpublication which introduces readers to the logistics development in China for this pivotal period. The papers are founded on the up-to-date studies of a team of dedicated researchers, and supported by the reputable Logistics Research Center at Nankai University. The book presents a comprehensive and thorough analysis of the progression and transformation of modern-day logistics in China, as well as the critical issues and perspectives involved in it. Researchers and practicing professionals alike will find this book an indispensable and (3z(Bjust-in-time(3y (Breference and information resource.s
Development Environment of China Logistics -- Development Status of China$1 (Bs Logistics Market -- Development Status of China$1 (Bs Logistics Infrastructure -- China$1 (Bs Logistics Development in Certain Key Regions -- Logistics Development in Some Key Industrial Segments -- Hot Issues in China$1 (Bs Logistics Development -- Conclusions and Outlook.s
Keywords: Economics; Economics/Management Science; Production/Logistics/Supply Chain Management